Mitochondrial genomes of five Hyphessobrycon tetras and their phylogenetic implications. Issue 18 (11th August 2021) - Xu, Wei; Lin, Shupeng; Liu, Hongyi
Abstract: To date, the taxonomic status and phylogenetic affinities within Hyphessobrycon, even among other genera in Characidae, remain unclear. Here, we determined five new mitochondrial genomes (mitogenomes) of Hyphessobrycon species ( H. elachys, H. flammeus, H. pulchripinnis, H. roseus, and H. sweglesi ). The mitogenomes were all classical circular structures, with lengths ranging from 16, 008 to 17, 224 bp. The type of constitutive genes and direction of the coding strand that appeared in the mitogenomes were identical to those of other species in Characidae. The highest value of the Ka/Ks ratio within 13 protein‐coding genes (PCGs) was found in ND2 with 0.83, suggesting that they were subject to purifying selection in the Hyphessobrycon genus. Comparison of the control region sequences among seven Hyphessobrycon fish revealed that repeat units differ in length and copy number across different species, which led to sharp differences in mitogenome sizes. Phylogenetic trees based on the 13 PCGs did not support taxonomic relationships, as the Hyphessobrycon fish mixed with those from other genera. These data were combined to explore higher level relationships within Characidae and could aid in the understanding of the evolution of this group. Abstract : To date, the taxonomic status and phylogenetic affinities within Hyphessobrycon, even among other genera in Characidae, remains unclear. Here, we determined five new mitochondrial genomes of Hyphessobrycon species.